1970
DOI: 10.1104/pp.46.5.728
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Plant Water Relations with Divided Root Systems of Soybean

Abstract: Soybean (Glycine max) was grown with root systems divided between adjacent cartons containing nutrient solution or soil. By adding polyethylene glycol (Carbowax 6000) to reduce solute potential or withholding water to reduce soil matric potential until water absorption from that side stopped, the root xylem water potential could be ascertained. Carbowax appeared to increase root resistance. An imbalance technique is described with which soil moisture contents of adjacent containers were followed individually. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

1971
1971
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…Lawlor (1973) found that the growth of seminal roots of wheat (Triticum aestivum cv Kolobri) decreased with decrease in osmotic potential of PEG 1500 and stopped completely at -1.0 MPa. Similar reductions in root elongation due to osmotic stress by PEG have been reported by other authors (Coutts, 1982;Kawasaki et al, 1983;Michel and El Sharkawi, 1970). Newman (1966) showed that the growth of individual roots of flax (Linum usitatissimum) was a function of the water potential of the soil close to the root tips.…”
Section: Introductionsupporting
confidence: 79%
“…Lawlor (1973) found that the growth of seminal roots of wheat (Triticum aestivum cv Kolobri) decreased with decrease in osmotic potential of PEG 1500 and stopped completely at -1.0 MPa. Similar reductions in root elongation due to osmotic stress by PEG have been reported by other authors (Coutts, 1982;Kawasaki et al, 1983;Michel and El Sharkawi, 1970). Newman (1966) showed that the growth of individual roots of flax (Linum usitatissimum) was a function of the water potential of the soil close to the root tips.…”
Section: Introductionsupporting
confidence: 79%
“…The relationship between soil water potential and flux in one part influenced soil water potential of the other part, due to apparent hydraulic connection through the root system (Simonneau & Habib 1994). When water availability in one part of the root system decreases while the other part is kept well watered, water absorption by the well‐watered roots can increase even without a decrease in leaf water potential (Michel & Elsharkawi 1970; Tan & Buttery 1982; Simonneau & Habib 1994; Sakuratani, Aoe, & Higuchi 1999). A possible hypothesis explaining increased uptake in split‐root media is the onset of a flux from root in wet to root in dry medium (Simonneau & Habib 1994), but decreased hydraulic resistance in roots is a plausible alternative hypothesis (Morizet, Cruiziat, & Falcimagne 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The overall response has been investigated using splitroot experiments (Brouwer 1953;Herkelrath, Miller & Gardner 1977;So 1979;Tan & Buttery 1982;Morizet, Cruiziat & Falcimagne 1988;Neri & Flore 1990;So & Jayasekara 1991). When one part of a root system is subjected to a decreasing water availability while the other part is well-supplied with water, absorption by the well supplied roots increases (Brouwer 1953;Michel & ElSharkawi 1970;Tan & Buttery 1982;Morizet et al 1988). This is commonly attributed to a lessening of root hydraulic resistance (Morizet et al 1988) calculated by dividing the potential difference between the leaves and the nutrient solution by the measured transpiration.…”
Section: Introductionmentioning
confidence: 99%